Prevalence of urinary incontinence among young female adults - Muhammad Osama; Shaukat, Saman; Javed, Momnah; Naeem, Maryam (Journal of the Pakistan Medical Association, 2022)
A cross sectional survey was conducted in 2018-2019 to determine the prevalence of urinary incontinence among university going nulligravid young female adults in Rawalpindi/Islamabad, Pakistan. A total of 608 participants were included in the study via convenience sampling. Data was collected regarding demographic and personal information, in addition to Medical, Epidemiologic, and Social Aspects of Aging (MESA) Urinary Incontinence Questionnaire (UIQ). Independent t-test and One-way ANOVA were used for inter-group comparisons. Pearson and Spearman correlation was used to determine the relationship between variables. The overall prevalence of urinary incontinence was observed to be 31.7% (n=193), and of stress, urge and mixed incontinence was found to be 10.5% (n=64), 9.2% (n=56) and 12% (n=73) respectively. A significant difference (p<0.05) was observed in terms of MESA-UIQ stress incontinence and urge incontinence scores based on tobacco use, menstrual disorders, eating disorders and marital status. Keywords: Epidemiology, urinary incontinence, stress incontinence, urge incontinence, young adults, prevalence, nulligravidity.